Design of the Gear Fault Test System based on the Method of Transmission Error Detection - Wang Bolei; Cui Yanping; Lu Zhaojing (Jixie chuandong)
The method of transmission error detection is applied to gear fault diagnosis,the transmission error signal of the gear system is obtained by measuring pulse width time of the gearbox shaft angular encoder output two square wave pulse.Secondly,the transmission error signal is decomposed into a finite number of intrinsic mode components（IMF） by the method of empirical mode decomposition,and then the IMF component containing the most dominant fault information are filtrated to merged into a new signal.Finally,the order analysis and spectrum analysis on the new signal is carried out,the fault characteristics are obtained and gear fault diagnosis is realized.The designed two channel data acquisition card is applied to build up the gear fault analysis test system based on the method of transmission error detection.The experiment results show that the gear fault analysis test system can be effectively diagnose the gear fault.